Extra up-spin magnetic moments and extraordinary high saturation magnetization of Ni2+ doped barium ferrite in 4f2 site. (15th May 2019) - Wang, Min; Xu, Qiankun; Liu, Jian; Wang, Zongrong; Ma, Ning; Du, Piyi
Abstract: It is vital important to explore excellent magnetic property other than outstanding dielectric property in multiferroic barium ferrite. Herein, BaFe12−x Nix O19 (x = 0 ∼ 1.0) ceramics are prepared successfully by sol-gel method. The effects of Ni 2+ doping on the formation, magnetic properties of BaFe12−x Nix O19 ceramics are investigated. Results show that Ni 2+ ions substitute Fe 3+ in 4f2 site, making neighbor Fe 3+ to be transformed into Fe 2+ . Effective up-spin magnetic moments per molecule, which determine the magnetization of the ferrites, are increased theoretically from 20 μ B to 28 μ B . With Ni 2+ doping, grain size is promoted to be large enough to neglect approximately restriction of grain boundary on reaching theoretical saturation magnetization (Ms ) of ferrites. Relatively low anisotropic field of ∼14 kOe and coercivity of ∼306 Oe, and extremely high Ms of ∼100.9 emu g −1 are exhibited in BaFe11.2 Ni0.8 O19 ceramics. The Ms of ∼100.9 emu g −1 is ∼40% higher than theoretically optimal Ms of undoped ferrites, providing it larger possibility to increase magnetization and broadening its applications in electronic devices.